Ion Electric Propulsion System Electric Breakdown Problems: Causes, Impacts and Protection Strategies - Zheng Peng; Zongliang Li; Fei Song; Yu Zhang; Huan Xi; Feng Liu (IEEE Access, 2023)
Ion electric propulsion systems have been widely used in satellite station keeping, attitude control, and orbit transfer due to their advantages of high specific impulse, good flexibility, and high reliability. The electric breakdown might happen at grids or across isolators due to the disturbing effects of the power source or environment. The electric breakdown can induce spurious effects in the power processing unit (PPU) circuit from the return currents and voltage drops, which could be several orders of magnitude higher than the impulses at normal working conditions. When the electric breakdown happens, it might result in serious electromagnetic interference and damage to the electric and electronic equipment in the spacecraft. This paper provides a comprehensive summary of the various factors that can cause electric breakdown in an ion electric propulsion system, such as environmental factors, manufacturing considerations, and operational conditions of the thruster. Furthermore, a comprehensive analysis of the impact of electric breakdown on the ion thruster, electric propulsion system, and spacecraft mission is explored. The effectiveness of different grounding configurations in safeguarding against ion thruster electric breakdown has also been evaluated. Based on the analysis and discussion, the control and protection strategies are proposed for the ion electric propulsion system electric breakdown problems.